The role of video-based discussion in model for preparing professional development leaders - Hilda Borko; Janet Carlson; Charmaine Mangram; Robin Anderson; Alissa Fong; Susan Million; Suki Mozenter; Anthony Muro Villa (SpringerOpen, 2017)
Abstract Background This paper describes the Problem-Solving Cycle model of professional development and the Mathematics Leadership Preparation model of PD leader preparation. These models form the backbone of our current research-practice partnership project in which we are working with a large urban district to adapt these models to develop district capacity to support the implementation of a middle school mathematics curriculum aligned with Common Core State Standards (CCSS). We highlight the central role of video in the Problem-Solving Cycle and our approach to preparing teacher leaders to use video-based discussions to understand student thinking and instructional practices. Results The first phase of the research was designed to identify how the models were adapted to support the district goals for implementing their new CCSS mathematics curriculum and to understand the reasons for the adaptations. The analysis of multiple data sources revealed two overarching categories of adaptations that we made to refine the models to better support the district goals: addressing district priorities and addressing teacher leaders' limited experience. We made adaptations such as incorporating the district curriculum, addressing the needs of English learners, integrating the teacher leaders' learning of the Problem-Solving Cycle model into the leadership preparation session, increasing the emphasis on what it means to be an instructional leader, strengthening the role of modeling and debriefing activities to support leadership development, scaffolding the selection of video clips, and incorporating the use of rehearsals and debriefing activities to support leadership development. Conclusion The implications of this work illustrate the need for researchers to be responsive to the context of their school partners if they expect their work to be meaningful. Using the frame of design-based implementation research proved to be an effective strategy for working with the district STEM leadership team and teacher leaders to adapt the Problem-Solving Cycle and Mathematics Leadership Preparation models to support district implementation of a new curriculum that necessitates shifts in teacher practices and for determining how to make video-based discussions more productive activities in the models.